The impact of new media advertising on consumer decision making process / Syuhaida Shaiful Anuar - Shaiful Anuar, Syuhaida (2019)
The purpose of this research is to examine the impact of new media advertising on consumer decision making process. The importance of this present as well as the research's goal to ensure the research on the impact of new media advertising on consumer decision making process. The survey will found that whether the consumer making decision process and more likely to consume new media advertising but this research does not only find the factor, characteristics and commonness of new media advertising could be the cause of consumer decision making process but however, in nature, both consumption of new media advertising and consumer decision making process is relate to each other. The research gives explanation on how consumers are attending, processing and selecting the information on new media advertising before making a purchase. The findings indicated that consumers pursue an active role in information search on new media advertising compared to mass media, yet information exposure is selective and subjective during the course of information search. Moreover, the implication of the research showed that the empirical part was able to help any companies that are trying to shift to or are currently participating in the new advertising trend.